Penerapan Metode Qira’ati Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Anak Di Majelis Nurul Huda - Maturidi; Rois, Ajun; Mustaqim, Ismail; Herlina, Herlina; Asila, Reni Nurul; Damayanti, Suci (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to examine the implementation of the Qira’ati method in improving children’s ability to read the Qur’an at Majelis Nurul Huda. The research method employed is a qualitative approach with a descriptive method, with the research subjects being children participating in Qur’an learning, and the research object being the process of implementing the Qira’ati method. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques, supported by source and technique triangulation to maintain data validity. The findings show that the Qira’ati method is effective in helping children recognize hijaiyah letters, read with tartil, and observe tajwid rules. Moreover, this method fosters self-confidence, discipline, and independent learning in children. Supporting factors include student motivation, the teacher’s role as facilitator and motivator, and a conducive learning environment, while obstacles consist of differences in children’s abilities and limited facilities. Thus, the Qira’ati method is recommended as an effective alternative for Qur’an learning, both in formal and non-formal institutions, as it has been proven to improve technical reading skills while shaping positive attitudes in children.